Comprehensive cDNA cloning and putative feature analysis of endogenous cellulases possessed by the Pacific oyster, Crassostrea gigas. - Manabu Wen-Liu Tanimura; Kazuhiko Koike; Motoki Kayama; Kazumi Matsuoka (PLoS ONE)
Previous studies have examined the cellulase activity of Crassostrea gigas (Pacific oyster) and suggested its potential utilization of terrestrial lignocellulose. However, no studies have been conducted to comprehensively assess its endogenous cellulases. Therefore, our objective was to identify the cellulases present in C. gigas through transcriptome and genomic analyses. The results showed that there are 10 cellulase orthologs, seven of which are endogenous. Phylogenetic analysis revealed that two of these cellulases belong to the glycoside hydrolase family (GHF) 5, four to GHF9, and one to GHF45. An alignment of the amino acid sequences suggested the presence of at least endo-β-1,4-glucanase. Therefore, C. gigas is likely capable of decomposing lignocellulose into glucose. This finding supports the fact that C. gigas, a globally commercial bivalve species, thrives in environments that lack phytoplankton, such as mangroves.